First record of Lutjanus xanthopinnis (Actinopterygii: Perciformes: Lutjanidae) from the Andaman Islands, India - J. Praveenraj; N. Daniel; R. Kiruba-Sankar; S.S. Mishra (Acta Ichthyologica et Piscatoria, 2018)
The majority of morphological abnormalities reported for elasmobranchs are cases of bicephalia. This contribution describes the third confirmed case worldwide and the first This study provides the first record of Lutjanus xanthopinnis Iwatsuki, Tanaka et Allen, 2015 from the Andaman Islands. The new record is based on 2 specimens, 123 and 154 mm SL, captured inshore of Dignabad, Port Blair, Andaman Islands, India. The fish were examined, described, and illustrated. Morphometric and morphological data confirmed that the specimens examined from the Andamans are L. xanthopinnis, which varies distinctly from a closely-related species Lutjanus madras (Valenciennes, 1831).